Economic valuation for water supply from Merapi Volcano National Park Case study: Kali Kuning sub watershed - Ayu Diyah Setiyani; Charlotte de Fraiture; Robiyanto Hendro Susanto; Annelieke Duker (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
The Merapi Volcano National Park (MVNP) is developed based on particular considerations such as protecting ecosystem or preserving certain species. Management of national park will not succeed unless the communities surrounding park support the park itself. However, it will be challenging because the park was established through a ‘top-down’ process. Therefore, it is important to ensure that the surrounding communities are able to derive benefit economically from the park, especially environmental services such as water supply. The goal of this study is to estimate the economic value for water supply from MVNP with Kali Kuning Sub Watershed as the study case. The economic valuation is estimated based on three different land use maps: 2015’s (deforestation), 2025’s (afforestation) and extreme condition which is grassland (without national park). The economic value is approached by market price for water use value. Lastly, cost and benefit analysis based on several scenarios (deforestation, afforestation and ‘without national park’) is implemented. The study shows that afforestation scenario presents the highest economic value from water supply for the surrounding communities as well as the downstream communities.